Recent Advances on Cellulosic Emulsions for Encapsulation of Bioactive Substances - Xiang LI; Yuanjun SUI; Yifan PANG; Jia WEI; Hui ZHOU; Yunhai HE; Dandan REN; Shu LIU; Long WU (Shipin gongye ke-ji, 2024)
Protection, dispersion and delivery of the functional components can implement in the emulsion-encapsulating systems. Among the stabilizers of the emulsion, specific structure of the cellulose may improve the stability of the system, and supplying the utilization of the bioactive substances on encapsulation and release. Therefore, the recent advances on stabilizing mechanism, cellulosic materials, properties of bioactive substances and factors affecting on the release of cellulosic emulsion-encapsulating systems are summarized in this review. In addition, the paper focuses on the release process and regulated mechanism of cellulose, which shows high length-diameter ratio and mechanical strength in the emulsion-delivery system of bioactive substances, and providing reference for the development of the food-grade delivery system. Studies indicates that cellulose-stabilized emulsion can improve the dispersion and oxidation stability of the bioactive substances, while controlling the release and improving the bioavailability of the functional factors. However, there is still vast research space for its safety evaluation in the food system, and related toxicological experiments urgently need to be carried out.